Current Trends in Web Engineering ICWE 2013 International Workshops ComposableWeb, QWE, MDWE, DMSSW, EMotions, CSE, SSN, and PhD Symposium, Aalborg, Denmark, July 8-12, 2013. Revised Selected Papers - Sheng, Quan Z.; Kjeldskov, Jesper (Information Systems and Applications, incl. Internet/Web, and HCI ;, 2013)
This book constitutes the thoroughly refereed post-proceedings of the seven workshops and the PhD Symposium that were co-located with the 13th International Conference on Web Engineering, ICWE 2013, held in Aalborg, Denmark, in July 2013. The papers cover research in topics such as social data management; cloud service engineering; agile web development; and quality management in web engineering.